Correlation Between Body Weight Day Old Chick (DOC) and Body Weight Each Week from Commercial Farms in Province of Rizal, Philippines - G. S. Payte; L. Purnamasari; J. P. Olarve; N. J. P. de Leon; J. F. dela Cruz (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2022)
Farmers of the poultry industry are seeking new and more efficient techniques to produce broilers more quickly, without sacrificing quality, nutrition, or cost, as the demand for poultry rises in conjunction with the human population. This study analyzed the weight of broilers from day 1 to harvest day to determine the impact of each daily or weekly weight on the final weight of the broilers. The experiment was conducted in a conventional type of housing. One hundred thousand male Cobb strain day-old chicks were housed. The feed of the chicks consisted of commercially blended feeds including CP and BMEG, as well as vitamins, minerals, and amino acids, in accordance with nutritional needs. The study examined the relationship between the day-old chick’s weight and the flock’s weekly weight and discovered that there is no correlation between the day-old chick’s weight and its weekly weight at days 7, 14, 21, 28, and 35 (harvest weight). However, the weight at the 7-day mark had the greatest effect on the potential market weight of the broiler. It can be determined that the early life of chickens plays a crucial role in their productivity.